SOSIALISASI GERAKAN EDUKASI MENABUNG ANAK SEKOLAH (GEMAS) DENGAN MEMBAGIKAN CELENGAN UNTUK MENINGKATKAN KREATIVITAS SISWA KELAS 4 MI MA’UNAH SARI DESA TANAH ABANG - Sintia Jasmuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Socialization is one of the important methods in the educational process, where its purpose is to provide understanding of a certain concept or practice to individuals or groups within society. One relevant example of socialization is the introduction of the importance of saving in financial management. Saving is an activity that involves setting aside a certain amount of money over a period of time to be used in the future. The importance of financial understanding applies not only to adults or parents but also to young children. Therefore, it is essential to provide understanding and build good habits from an early age that will be beneficial in the future. The purpose of this saving socialization activity is to train school children to set aside part of their money for savings.